Sin and Divine Punishment: The Korean series Jiok (Hellbound, KR 2021-), New Religious Movements, and a World Full of Guilt - Winter, Franz (Journal for religion, film and media, 2023)
The TV series Jiok (Yŏn Sang-ho, KR 2021-), internationally known as Hellbound, is a recent and highly successful series that has been available on the streaming platform Netflix since November 2021. It is usually described as a "dark mystery thriller" or "dark fantasy film", which points to the general tone but also to its constant interplay with the "mysterious". The plot revolves around the appearance of monstrous creatures who suddenly arrive out of nowhere and kill people in a most brutal and bloody way. All of those who are killed in this heinous manner have received a warning beforehand, delivered by "angels" foretelling their fate and their imminent death and introducing crucial topics such as "guilt" and "sin" as a reason for the whole procedure. The article introduces major topics of this series and focusses on the prominent role of a new religious movement that is intimately linked to major trajectories of the plot.